(2n^3 + 4n^2 - 7) + (-n^3 + 8n - 9)

(2n^3 + 4n^2 - 7) + (-n^3 + 8n - 9)
= 2n^3 + 4n^2 - 7 - n^3 + 8n - 9
= n^3 + 4n^2 + 8n - 16 (final answer)

Expert answered|Andrew.|Points 51602|

Question

Asked 5/8/2015 10:22:22 AM

Updated 5/8/2015 2:31:50 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

Rating

There are no new answers.

Evaluate the following expression.
(-6)^-2

Question

Not Answered

Updated 5/4/2015 12:54:35 PM

1 Answer/Comment

Find the quotient.
(42j^4k^2) ÷ (-3j^3k)

Question

Updated 5/8/2015 11:50:42 AM

1 Answer/Comment

x^0 + y^0 for x = 3 and y = 2;

3^0 + 2^0

= 1 + 1

= 2

3^0 + 2^0

= 1 + 1

= 2

Added 5/8/2015 11:50:42 AM

This answer has been confirmed as correct and helpful.

Simplify the expression.
2(3y - 7) - 5y(2 - y) **Weegy:** 2(3y - 7) - 5y(2 - y) = 6y - 14 - 10y + 5y^2 = 5y^2 - 4y - 14 **User:** Find the product.
(n + 8)(n - 2) **User:** Use the definitions and theorems of this section to evaluate and simplify the following expression. Be sure to express answers with positive exponents.
(b 4) 2 (More)

Question

Not Answered

Updated 5/8/2015 2:09:53 PM

2 Answers/Comments

(n + 8)(n - 2) = n^2 - 2n + 8n - 16 = n^2 + 6n - 16

Added 5/8/2015 2:08:36 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/8/2015 2:09:42 PM]

Find the product mentally.
(r - s)^2 **Weegy:** (r - s)^2
=r^2 - rs - rs + s^2
=r^2 - 2rs + s^2 **User:** Find the product mentally.
(2m - 9)^2 **User:** Find the product mentally.
(ab + 3)^2 **Weegy:** (ab + 3)^2
=(ab + 3)(ab + 3)
=(ab)(ab) + (ab)(3) + (3)(ab) + (3)(3)
=a^2b^2 + 3ab + 3ab + 9
=a^2b^2 + 6ab + 9 **User:** Find the product.
(n + 7)^2 (More)

Question

Updated 5/5/2015 1:39:25 PM

3 Answers/Comments

(2m - 9)^2

= (2m - 9)(2m - 9)

= 4m^2 - 18m - 18m + 81;

= 4m^2 - 36m + 81

= (2m - 9)(2m - 9)

= 4m^2 - 18m - 18m + 81;

= 4m^2 - 36m + 81

Added 5/5/2015 12:59:49 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [5/5/2015 1:41:00 PM]

Find the sum of the given polynomials.
2mn + 4n 2 and 5m 2 - 7mn **Weegy:** 2mn + 4n2 + 5m2 - 7mn = 5m2- 5mn+ 4n2
**User:** Reduce -8 + b 2 by 5 + b 2.
**User:** Take -4 + 3a 2 from 7a - a 2. **Weegy:** (7a - a^2) - (-4 + 3a^2) = -4a^2 + 7a + 4
**User:** Find a - 2b + 3c diminished by a - 2b - 3c + d. **Weegy:** (a - 2b + 3c)-(a - 2b - 3c + d) = 6c - d
**User:** Find 2p^2 + 3p - 4 less - 2p^2 - 3p + 4.
**User:** After arranging the terms in descending powers of a variable, select the opposite of the polynomial.
9 - 12n 2 + 4n 3 - 7n **Weegy:** 9 - 12n^2 + 4n^3 - 7n = (n+1) (4 n^2-16 n+9)
**User:** Simplify 3j - {2k - [5h - (3j + k)]}. **Weegy:** 3j - {2k - [5h - (3j + k)]} = 5h - 3k
**User:** Find x - y less than 0. **User:** Simplify 2m - [n - (m - 2n)]. (More)

Question

Not Answered

Updated 6/6/2015 12:33:30 PM

3 Answers/Comments

-8 + b - (5 + b^2)

= -8 + b - 5 - b^2

= -13 + b - b^2

= -8 + b - 5 - b^2

= -13 + b - b^2

Added 5/4/2015 7:24:26 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/6/2015 12:29:48 PM]

2p^2 + 3p - 4 - (-2p^2 - 3p + 4)

= 2p^2 + 2p^2 + 3p + 3p - 4 - 4

= 4p^2 + 6p - 8

= 2p^2 + 2p^2 + 3p + 3p - 4 - 4

= 4p^2 + 6p - 8

Added 5/4/2015 7:26:36 PM

This answer has been confirmed as correct and helpful.

2m - [n - (m - 2n)]

= 2m - [n - m + 2n]

= 2m - 3n + m

= 3m - 3n

= 2m - [n - m + 2n]

= 2m - 3n + m

= 3m - 3n

Added 5/4/2015 7:28:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/6/2015 12:34:48 PM]

31,989,235

questions answered

There are no comments.